Development of Wheat Straw Fortification Machine - Garg, M K; Lohan, O P; Jain, S (Journal of Agricultural Engineering, 2005)
Traditionally, mixing of wheat straw and molasses in the country is practised by hand which is time consuming and results in hand injuries. To overcome this problem, a batch type feed mixer was developed for uniform mixing of wheat straw and molasses. This machine mixed about 50 kg of wheat straw with molasses uniformly in 10 to 15 minutes. The output capacity of the machine was 200 kg/hr.